Enhancing Immediate Implant Success - Ahmed Shefaa H. Alnuamy; Ihsan A. Kumail; Salam K. Rasheed; Hasan Skienhe (Dentistry 3000)
Objective: This study evaluated the effectiveness of bone substitutes and local antibiotics in enhancing osseointegration during immediate implantation in fresh extraction sockets. Material and Methods: A total of 30 patients underwent immediate implant placement, divided into three groups: control group receiving no adjuncts, group treated with bone substitutes, and group treated with bone substitutes combined with antibiotics. After four months, success rates were assessed through implant stability quotient (ISQ) measurements. Results: The current findings indicated significantly higher success rates in the groups receiving adjunct treatments than in the control, highlighting the potential of bone substitutes and antibiotics in promoting favorable outcomes. Conclusion: This study underscores the importance of personalized treatment approaches that consider patient-specific factors and the use of adjunctive therapies to optimize implant success.